Pemberdayaan Anak Korban Perceraian Melalui Pengolahan Hasil Laut Berbasis Online Menuju Kemandirian Ekonomi Kreatif - Fauzi, Fathul; Fanan, M Athoiful; Amriana, Amriana (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
This assistance aims to determine the form and impact of empowering children who are victims of divorce in the Ujung Pangkah Gresik sub-district through online-based processing of seafood towards creative economic independence. From this assistance, it is hoped that it will be able to create economic independence for children who are victims of divorce and it is hoped that it will be able to suppress the destructive potential that befalls children who are victims of divorce. The problem formulation of this assistance is what is the form and impact of Empowering Children of Divorce Victims in Ujung Pangkah Gresik District through Online-Based Sea Product Processing Towards Creative Economy Independence? This assistance uses an Asset Based Community Development (ABCD) approach and is carried out in Ujung Pangkah Gresik District. This assistance involved 15 children who were victims of divorce in Ujung Pangkah Gresik District. It can be concluded that this form of empowerment assistance through making products from marine products in Ujung Pangkah Gresik District is able to provide change for children who are victims of divorce. There are three products produced and marketed, namely crackers, ebi shrimp and fish chunks. The impact of this assistance on children who are victims of divorce is that they have had positive activities so that they no longer track, consume drugs and buskers. Apart from that, this assistance can increase the creative economic independence of children who are victims of divorce.